1969
DOI: 10.1021/bi00829a021
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of cytochrome c with imidazole

Abstract: Ferricytochrome c binds imidazole and 1-methylimidazole in reactions with 1:1 stoichiometry. The pH and temperature dependence of imidazole binding indicate that the reaction is analogous to the binding of the enzyme by ligands such as cyanide and azide. At pH 7.4 and 18°the observed thermodynamic parameters for imidazole binding are: AF = -1.9 kcal/mole, AH = +1.1 kcal/mole, and AS = +10.2 eu. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 13 publications
4
46
0
Order By: Relevance
“…This is in agreement with the findings of Schejter & Aviram (1969) who found a preferential binding of imidazole to the cytochrome in the Fe 3~ oxidation state of the heine iron.…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with the findings of Schejter & Aviram (1969) who found a preferential binding of imidazole to the cytochrome in the Fe 3~ oxidation state of the heine iron.…”
Section: Resultssupporting
confidence: 93%
“…We observed that while 30% of cyt c 1 retained a midpoint potential comparable to the value found for highly active bc 1 complex (250 -270 mV), 70% showed a lower midpoint potential of 146 Ϯ 6 mV. It has been shown that imidazole can displace the methionine axial heme iron ligand of cyt c (27) and that this type of ligand substitution is accompanied by a decrease in the midpoint potential of the heme (28). We suggest therefore that a similar ligand substitution occurs in cyt c 1 of the bc 1 complex when imidazole is used in the purification procedure.…”
Section: Polypeptide Composition and Aggregation Statesupporting
confidence: 56%
“…Also the spectrum of the reduction product obtained within 1 min of mixing is that of ferrocytochrome c. These observations do not, however, necessarily argue against our interpretation, since the loss of S(IV) [presumably 0-bonded as sulfite to Fe(JI)] is expected to be very rapid. Thus the rate of release of X from X-FeIIcyt c is 8.8 X 10-4 secat 250 when X = CO (14), 4.27 X 10-3 sec' at 25°when X = CN- (14), and 1.08 X 10-1 sec-1 at 21°when X = imidazole (15). As this order probably parallels the affinity of Felicyt c for X, and the affinity of Fe cyt c for oxygen-bonded Jigands is expected to be small, rapid dissociation of sulfite-Felicyt c is not surprising.…”
Section: Remote Attack Pathwaymentioning
confidence: 95%